Flexible Work Arrangements and Employee Perfomance: A Study with Biblioshiny - Hariyanto, Adna Moria; Hanoum, Syarifa; Nikmah, Uliyatun (Jurnal Sains dan Seni ITS, 2024)
This study investigates the thematic evolution in the research of flexible work arrangements and employee performance, with data from the Scopus database, spanning from 1989 to 2023, also with a particular focus on the impact of the COVID-19 pandemic and the widespread implementation of work-from-home policies. The research documents a signifi-cant increase in scholarly articles from 2020 to 2023, indicat-ing heightened academic interest in this field. Through the-matic mapping and analysis, the study categorizes the research themes into four distinct groups: motor themes that propel the field, niche themes that concentrate on specific issues, emerg-ing or declining themes that reflect changing research inter-ests, and basic or transversal themes that are consistently prevalent. The findings highlight the enduring significance of flexible work arrangements and employee performance as a subject of research, suggesting that these themes will continue to be important as the nature of work evolves in response to global events and technological advancements. The study pro-vides a comprehensive overview of the current state of re-search and points to the necessity for ongoing investigation into how flexible work arrangements can be optimized to sup-port employee performance in a post-pandemic world.